Analisis Hasil Uji Tarik Pada Sambungan Las Shield Metal Arc Welding (Smaw) Dengan Variasi Ketebalan Baja Mild Steel - Yusuf Satrio Wibowo; Xander Salahudin; Catur Pramono (ULIL ALBAB : Jurnal Ilmiah Multidisiplin, 2023)
The Shield Metal Arc Welding (SMAW) welding technique is the main alternative in working on steel construction on light vehicle frames. The mild steel used is a low carbon content steel which is known to have good mechanical properties. The purpose of this study was to analyze the results of SMAW welding with variations in the thickness of mild steel on the results of the tensile strength test and damage to the material after the tensile test was carried out. The research method used SMAW welding with a current of 35 A and E6013 electrodes and variations in material thickness of 1.0 mm, 1.5 mm, 2.0 mm, 2.5 mm and 3.0 mm. The test standard used is ASTM E8. Based on the research that has been done, the results of welding on 1.0 mm thick material having the highest tensile strength of 360.206 MPa, and 1.5 mm thick material having the highest tensile strength of 326.653 MPa, and 2.0 mm thick material having a tensile strength the highest tensile strength is 491,800 MPa, and the 2.5 mm thick material has the highest tensile strength of 416.481 MPa, while the 3.0 mm thick material has the highest tensile strength of 405 MPa. The greatest tensile strength is obtained when the material is 2.0 mm thick, while the smallest tensile strength is obtained when the material is 1.5 mm thick.